RISK FACTORS OF ABNORMAL UTERINE BLEEDING (OVULATORY DYSFUNCTION) IN REPRODUCTIVE-AGE WOMEN LIVING IN THE ANDIJAN REGION OF THE REPUBLIC OF UZBEKISTAN - Parpieva, Sh.O.; Yakubova, O.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Abnormal uterine bleeding (AUB) is a common multifactorial problem in reproductive health. This retrospective study analyzed 100 cases of women aged 18–45 years with ovulatory-related AUB in the Andijan region. Key risk factors included obesity (45 %), physical inactivity (55 %), hypothyroidism (30 %), and polycystic ovary syndrome (25%). Comorbid diabetes and hypertension were also observed. Findings underscore the importance of early diagnosis and tailored preventive strategies.